First record of Symphyla (Myriapoda) from Iran, with description of a new species in Scolopendrellopsis (Scolopendrellidae) - Scheller, Ulf; Kavianpour, Mohammad Reza; Esfandiari, Mehdi (Zootaxa, 2011)
The first species of Symphyla was described in 1763 and many hundreds of papers on the group have since appeared with almost 200 species having been described. However, very few of them deal with material from Asia (Scheller, 1971, 1988, Scheller & Golovatch, 1982, Scheller & Mikhaljova, 2000) and not a single species has been recorded from Iran. Now one of us (M.R. Kavianpour) has collected them for the first time from there. They appeared in a study of soil-living mites in gardens with pomegranates and grapes in the vicinity of Shahreza in the Esfahan Province, about 500 km south of Teheran, 1800 m asl., and were obtained from Berlese extractions of soil samples down to a depth of 20–30 cm.